Trends in Breast Cancer Incidence and Stage Distribution Before and During the Introduction of the Mammography Screening Program in Lithuania. (4th January 2019) - Steponaviciene, Laura; Briediene, Ruta; Vanseviciute, Rasa; Smailyte, Giedre
Background: The aim of this study was to analyze the incidence trends of localized and advanced breast cancer (BC) before and during the implementation of the mammography screening program (MSP) in Lithuania. Methods: The study period was divided into 2 intervals: the prescreening period (1998-2005) and implementation period (2006-2012). Analysis was performed for 3 age-groups: 0 to 49 years, 50 to 69 (target population), and older than 70. Results: In all age-groups, the incidence of localized BC has shown a steady increase, while the incidence of advanced stage BC has decreased. In the target population, during the study period, the stage I BC incidence increased statistically significantly by 10.3% per year (from 3.3 per 100 000 in 1998 to 12.2 per 100 000 in 2012). The increase in localized BC was faster in the period before the implementation of the MSP than during the implementation in 2006 to 2012 (10.3% and 5.7%). A slightly statistically significant decrease was observed for advanced BC during the study period (−1.1% per year), while during the implementation of the MSP, significant changes were not seen. Conclusions: The results of our study indicate that the implementation of the MSP in Lithuania did not significantly influence trends of localized and advanced BC. Changes observed during the study period, including the prescreening and screening introduction periods, may reflect the general trends in the awareness of BC and improvements in diagnostics.